Heptapartitioned Neutrosophic Soft Topological Spaces and Some Graphical Representation of Sternberg’s Triangular Theory of Love in terms of Heptapartitioned Neutrosophic Soft Sets with the Applications of Some Advanced Machine Learning Techniques (European Journal of Pure and Applied Mathematics, 2025)
The most generalized form of the soft neutrosophic set used in this article is the single valued heptapartitioned neutrosophic soft set (HPNSS). A set theoretic research is completed and some operations on them are defined. We went on to do a thorough investigation on HPNSS and discovered a number of odd characteristics. We built heptapartitioned neutrosophic soft topological spaces (HP-NSTS). Characterization of triangle theory of love is addressed with the help of HPNSTS. Heat map is developed for young boys and young girls separately. The normalized correlation matrix heat map (NCMHM) for young boys and girls is discussed. The analyzation and visualization of the correlation matrix of a data set containing data for Sternberg’s Eight Types of Love for young boys and girls is addressed. K-mean-HPNS-clustering is applied to group the data into K clusters. The elbow approach is used to determine the optimal number of clusters (K) for the K-mean clustering algorithm.
Keywords: Neutrosophic soft set, HPNS points, HPNSTS, HPNS p-open set, set, ????-Means algorithm, machine learning techniques and Heatmaps.